Drivers, mechanisms, and thresholds of woody encroachment in mesic grasslands - O'Connor, Rory Charles (Kansas State University, 2019)
Over the past 130 years in the North American tallgrass prairie, dramatic changes in grassland extent, structure and function have resulted from cessation of fire, extirpation of native herbivores (grazers and browsers), and the fragmentation of the landscape. One consequence of these changes is woody encroachment, the increased cover and abundance of woody species in grasslands. Woody encroachment is a worldwide phenomenon, resulting from global drivers (increased CO₂ concentrations [CO₂], changes in climate) and local drivers (i.e. land-use history, habitat fragmentation, changes in herbivore diversity, and land management practices). In this dissertation, I investigated the role of fire and browsing (local drivers) on woody plant ecophysiology (Chapter 2 & 3). I then addressed how elevated [CO₂], and drought (global drivers) impact the growth and physiology of woody plant seedlings (Chapter 4). Chapter 5 reports on breakpoint models to identify temporal and spatial thresholds in ecosystems to help improve adaptive management. In Chapter 2, I observed that fire and repeated browsing significantly decreased Cornus drummondii canopy cover, ramet density, and root nonstructural carbohydrates. These results suggest the significance of both fire and browsing on reducing C. drummondii dominance in the tallgrass prairie. In Chapter 3, I tested the limited leaf homeothermy hypothesis (LLHH) which posits that leaves can thermoregulate during periods of high temperatures to maximize carbon gain. I used C. drummondii shrub islands to test LLHH. Tleaf was lower during the hottest parts of the day, had minimal spatial variability within the shrub islands, and had little to no variation between browsed and unbrowsed shrub islands. This regulation of Tleaf by C. drummondii suggests support for the LLHH via high rates of transpiration and low water-use efficiency. In Chapter 4, I investigated how increased [CO₂] and water stress impacted the growth and physiology of four woody encroaching species (C. drummondii, Rhus glabra, Gleditsia tricanthos, Juniperus osteosperma). I found that elevated [CO₂] ameliorated the conditions of drought for all species through tight regulation of stomatal conductance. Starch concentrations within leaf and stem tissues had variable responses to treatments based on the species. However, I did not observe any increases in total biomass in response to increased [CO₂]. These results demonstrate that these seedlings were resilient to water stress in conjunction with elevated [CO₂]. In Chapter 5, I developed a method to quantitatively estimate temporal and spatial thresholds using Bayesian breakpoint models. Both models estimated breakpoints and corresponding uncertainties. Breakpoints and the latent spatial interpolation of breakpoints were mapped. Mapping of spatial breakpoints will allow managers to track where thresholds were crossed to help allocate resources. Overall, the results from my dissertation highlight the key roles of local and global drivers on woody plant ecophysiology, and the mechanisms contributing to their ability to maximize carbon gain in fluctuating environmental conditions. My work also provided a framework for linking the knowledge of drivers and mechanisms to create quantitative models that can inform when and where thresholds occur for adaptive management of grassland ecosystems.
Keywords: Mesic grassland; Tallgrass prairie; Woody encroachment; Plant physiology; Ecological thresholds